Penerapan Model Pembelajaran Inkuiri Dalam Meningkatkan Motivasi dan Hasil Belajar IPA - Nurul Niarti (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This research is aimed at the use of inquiry method in science class V learning on light material and its properties. The subjects of this study are the students of class V second semester of SD Negeri 050756 Flow Two subdistricts Sei Lepan which amounted to 20 students consisting of male students 7 students and 13 students. The results showed that the students' motivation and learning outcomes have increased. The improvement of students' learning motivation from the initial condition of 30% or 6 students increased to 12 students or 60% and reached 100% of the 85% minimum limit that has been determined on the success criteria of the improvement process of learning in the second cycle, and the improvement of student learning outcomes from the average at initial condition of 56,00 increased to 64,00 in cycle I and at end of cycle II increased to 76,50 and learning completeness at initial condition as many as 4 students (20%), after improvement by applying method of inquiry in cycle I increased to 10 students or 50% and in cycle II increased again to 18 students or 90%. Based on the results of the above research can be concluded that learning by using inquiry method can improve the process, motivation and learning outcomes of students of class V SD Negeri 050756 Flow Two Semester 2 Year Lesson 2016/2017 on science lesson with light material and its properties Keywords: questions, learning motivation, learning outcomes Abstrak: Penelitian ini ditujukan pada penggunaan metode inkuiri dalam pembelajaran IPA kelas V pada materi cahaya dan sifat-sifatnya. Subjek penelitian ini adalah siswa kelas V semester 2 SD Negeri 050756 Alur Dua kecamatan Sei Lepan yang berjumlah 20 siswa terdiri dari siswa laki-laki 7 siswa dan perempuan 13 siswa. Hasil penelitian menunjukkan motivasi dan hasil belajar siswa mengalami peningkatan. Peningkatan motivasi belajar siswa dari kondisi awal sebesar 30% atau 6 siswa meningkat menjadi 12 siswa atau 60% dan mencapai angka 100% dari 85% batasan minimal yang telah ditentukan pada kriteria keberhasilan proses perbaikan pembelajaran pada siklus kedua, dan peningkatan hasil belajar siswa dari rata-rata pada kondisi awal sebesar 56,00 meningkat menjadi 64,00 pada siklus I dan pada akhir siklus II meningkat menjadi 76,50 serta ketuntasan belajar pada kondisi awal sebanyak 4 siswa (20%), setelah dilaksanakan perbaikan dengan penerapan metode inkuiri pada siklus I meningkat menjadi 10 siswa atau 50% dan pada siklus II meningkat kembali menjadi 18 siswa atau 90%. Berdasarkan hasil penelitian di atas dapat disimpulkan bahwa pembelajaran dengan menggunakan metode inkuiri dapat meningkatkan proses, motivasi dan hasil belajar siswa kelas V SD Negeri 050756 Alur Dua Semester 2 Tahun Pelajaran 2016/2017 pada pembelajaran IPA dengan materi cahaya dan sifat-sifatnya Kata kunci: pertanyaan, motivasi belajar, hasil belajar